Corrosion Behaviour of Stir Casted AZ31 Magnesium Alloy-CaSiO3 Compositesin an Aqueous Solution - Penugonda Suresh Babu, K. L. Narayana, V. V. Kondaiah (International Journal of Advanced Science and Technology, 2020)
In the present work, Calcium Silicate (CaSiO3)powder is mixed with magnesium alloy (AZ31)as additive with weight percentage of 2 to 8% and fabricated in five compositions of samples by stir casting process and are evaluated to find Corrosion Rate (CR) using an electrochemical workstation attached with corrosion cell where the specimen surface isdirectly exposed to 5% Sodium Chloride (NaCl) solution. Tafel and Nyquist plots are plotted for all samples, the corrosion rate is measured and results are tabulated. The results showed thatthe S-4 sample of composition of 6% Calcium silicate and 90% Magnesium alloy showed a very less corrosion rate compared to other compositions followed by S-3 which is a composition of 4% calcium silicate with 92% Magnesium alloy sample showed approximate value of corrosion rate as S-4 sample. By Electrochemical Impedance Spectroscopy (EIS) experiment, the initiation of process is occurred above zero for all the samples. In comparison of the Corrosion Potential (Volts, V) (Ecorr) value and Corrosion Current (milliAmps, mA)( Icorr)values, sample S-2 reacts fast in electrolyte compared to sample S-4 but the samples S-3 and S-1 shows an approximate values in Ecorr. Keywords: Calcium Silicate, Corrosion, Magnesium Alloy, Sodium Chloride, Stir Casting.